Targeting the BMP Pathway in Prostate Cancer Induced Bone Disease - Straign, Desiree M.; Ihle, Claire L.; Provera, Meredith D.; Owens, Philip (Frontiers in Endocrinology, 2021)
From the 33,000 men in the U.S. who die from prostate cancer each year, the majority of these patients exhibit metastatic disease with bone being the most common site of metastasis. Prostate cancer bone metastases are commonly blastic, exhibiting new growth of unhealthy sclerotic bone, which can cause painful skeletal related events. Patient’s current care entails androgen deprivation therapy, anti-resorptive agents, radiation, and chemotherapy to help control the spread of the cancer but little intervention is available to treat blastic bone disease. The transforming growth factor beta (TGFβ) and bone morphogenetic protein (BMP) pathways are known to regulate bone growth and resorption of destructive lytic bone lesions, yet the role of TGFβ/BMP signaling in prostate cancer blastic bone lesions are not fully understood. We hypothesized that to target the BMP/TGFβ pathway, a useful biomarker of bone lytic or blastic pathology would have superior response. We show distinct BMP vs. TGFβ signaling in clinical samples of human prostate cancer bone metastases with either lytic or blastic pathologies. BMPs exhibit distinct effects on bone homeostasis, so to examine the effect of BMP inhibition on healthy bone, we treated mice with the BMP receptor small molecule antagonist DMH1 and saw a modest temporary improvement in bone health, with increased trabecular bone. We next sought to use the BMP inhibitor DMH1 to treat bone metastasis seeded by a caudal artery injection of the lytic human prostate cell line PC3 in immunodeficient mice. The colonization by PC3 cells to the bone were restricted with DMH1 treatment and bone health was importantly preserved. We next proceeded to test BMP inhibition in an injury model of bone metastasis via intratibial injection of the MYC-CaP mouse prostate cell line into FVBN syngeneic mice. DMH1 treated mice had a modest decrease in trabecular bone and reduced lymphocytes in circulation. Taken together we show unique responses to BMP inhibition in metastatic prostate cancer in the bone. These studies suggest that profiling bone lesions can help identify therapeutic targets that not only treat the metastatic tumor but also address the need to better treat the distinct tumor induced bone disease.